25(OH)D-but not 1,25(OH)2D-is an independent risk factor predicting graft loss in stable kidney transplant recipients - Zeng, Shufei; Yang, Yide; Li, Shuping; Hocher, Carl-Friedrich; Chu, Chang; Wang, Ziqiang; Zheng, Zhihua; Krämer, Bernhard; Hocher, Berthold (Frontiers in medicine, 2023)
BackgroundVitamin D deficiency (VDD) or vitamin D insufficiency is common in kidney transplant recipients (KTRs). The impact of VDD on clinical outcomes in KTRs remain poorly defined and the most suitable marker for assessing vitamin D nutritional status in KTRs is unknown so far.MethodsWe conducted a prospective study including 600 stable KTRs (367 men, 233 women) and a meta-analysis to pool existing evidence to determine whether 25(OH)D or 1,25(OH)2D predicted graft failure and all-cause mortality in stable KTRs.ResultsCompared with a higher 25(OH)D concentration, a low concentration of 25(OH)D was a risk factor for graft failure (HR 0.946, 95% CI 0.912−0.981, p = 0.003), whereas 1,25 (OH)2D was not associated with the study end-point graft loss (HR 0.993, 95% CI 0.977−1.009, p = 0.402). No association was found between either 25(OH)D or 1,25 (OH)2D and all-cause mortality. We furthermore conducted a meta-analysis including 8 studies regarding the association between 25(OH)D or 1,25(OH)2D and graft failure or mortality, including our study. The meta-analysis results were consistent with our study in finding that lower 25(OH)D levels were significantly associated with the risk of graft failure (OR = 1.04, 95% CI: 1.01−1.07), but not associated with mortality (OR = 1.00, 95% CI: 0.98−1.03). Lower 1,25(OH)2D levels were not associated with the risk of graft failure (OR = 1.01, 95% CI: 0.99−1.02) and mortality (OR = 1.01, 95% CI: 0.99−1.02).ConclusionBaseline 25(OH)D concentrations but not 1,25(OH)2D concentrations were independently and inversely associated with graft loss in adult KTRs.
Gesehen am 10.07.2023